Assortative mating in Spain: Who marries whom, and how does it influence income and wealth inequality? - Silvia De Poli; Jorge Onrubia; Fidel Picos (European Commission, Joint Research Centre (JRC), 2024)
Assortative mating can exacerbate household income inequality within and between generations. While previous studies have shown that it raises income inequality, its effects on wealth inequality remain less explored due to data limitations. This study uses Spanish administrative microdata to assess how assortative mating influences income and wealth inequality, and to what extent taxes and benefits mitigate these disparities. We find a strong tendency for assortative mating, especially among couples at the top of the income and wealth distribution, which amplifies income and wealth inequality. Our analysis shows that the entire Spanish tax-benefit system reduces inequality to the (pre-tax) level of a hypothetical scenario of random mating. Our findings highlight the need to consider wealth, taxes, and benefits in addition to income to understand the full impact of assortative mating on household well-being and inequality. While wealth accounts only for 18.5% of the joint income-wealth at the time of marriage, it explains about 25% of the pre-tax inequality and 34% of the post-tax inequality. This is driven both by the high concentration of wealth at the top of the distribution and the low level of progressivity of wealth taxes compared to labour income taxes.
Keywords: 330